Food restriction affects circadian and photoperiodic response in black-headed munia (Lonchura malacca malacca). Issue 3 (3rd May 2016) - Kumar, Pawan; Pandey, Rohit K.; Bhardwaj, Sanjay K.
Abstract: We determined the effect of food restriction on locomotor activity pattern and gonadal growth on black-headed munia ( Lonchura malacca malacca ) exposed to12L:12D light–dark cycle. Two groups of male and female munia ( n = 5 pairs each) were exposed to 12L:12D (L = 265 lux; D = 0.3 lux) for day 1–7. On day 8, group one received 4 h food (ZT 0–4; ZT 0 = Zeitgeber time, light onset) and group two received food ad libitum (ZT 0–24 h). Locomotor activity pattern and gonadal growth were recorded over the experiment period of one year. Birds were highly active in group one, with a high daily and total activity. However, activity behavior was fully synchronized with light onset in the group two, when food was available ad libitum . Gonadal maturation was initiated in both the groups but the maturation of testis and ovarian follicle was noticed only in group two (food ad libitum ). It appears that food restriction affects the locomotor activity and gonadal growth in black-headed munia.